ANALISIS POLITIK DINASTI DI KABUPATEN KEDIRI - Novendra Bimantara; Priyatno Harsasto (Journal of Politic and Government Studies, 2018)
The implementation of direct elections aims to improve democracy in the region and is a manifestation of the implementation of a democratic system and produce quality and quality leaders but in Kediri Regency it is inversely proportional to the objectives of the actual elections and in Kediri Dynasty Political practice has been running for almost 20 years, arguably the Dynasty in Kediri Regency is the first and longest of its existence. Dynastic politics is a political phenomenon of the emergence of candidates from the family environment of the head of government in power or done by a family or close relatives. Maybe this is what some people think is very contrary to democratic principles. This study discusses how a dynasty happened, survived, developed a dynasty that can survive and thrive in the midst of ups and downs of democracy and some pros and cons of the election law and who are actors actors involved in a group called Political Dynasties. This research uses oligarchy, patron-client theory and political dynasties. The results of this study are how the beginning or history of this dynasty occurred starting from business affairs and then going towards politics, in the development of this dynasty only the closest people who according to Sutrisno's family were able and able to carry out or continue the programs that had been made and it has not yet been implemented and many relatives ranging from businessmen and officials from the village level to the high levels of the region are ready to help and serve the dynasty with the aim of getting a return.This dynasty will also continue to occur if the regulations or laws governing a democratic system do not experience a definite change. Because of its inclusive and closed nature, it makes a political dynasty very difficult to find a mistake. It is very difficult to uncover abusive practices of power in a closed group of people, because every individual tries to look after each other. At first glance there is nothing wrong with dynastic politics. Especially if referring to the democratic argument that every citizen has the same rights to be elected and elected. However, it cannot be denied that the political dynasties that have developed so far have hurt the essence of democracy itself.Keywords: Democracy, Dynasty Politics, Kediri Regency and Political